Anxiety-Related Bleeding and Thrombosis - Hoirisch-Clapauch, Silvia (Seminars in Thrombosis and Hemostasis, 2018)
Anxiety, a normal response to stressful situations, is characterized by increased levels of factor VIII, fibrinogen, and von Willebrand factor, and by enhanced platelet aggregability. One would expect acute anxiety to be a prothrombotic state, but since acute mental stress induces tissue plasminogen activator (tPA) release from endothelial and chromaffin cells, fibrinolysis counteracts procoagulant stimuli. It could be said that procoagulant changes accompanying the fight-or-flight response reduce the risk of bleeding in case of potential injuries, while activation of fibrinolysis counteracts activation of hemostasis to prevent intravascular thrombus formation before injuries occur. Acutely anxious patients are prone to bleeding or thrombosis when the balance between hypercoagulation and hyperfibrinolysis is disturbed. Acute anxiety not only increases the risk of bleeding in hemophilia or von Willebrand disease, but many reports have shown that anxiolytic interventions such as hypnosis are effective in controlling bleeding in hemostatic disorders. The pathogenesis of cardiovascular and thrombotic diseases in highly anxious patients is multifactorial. An important element is α-adrenergic vasoconstriction, which increases viscosity due to leakage of intravascular fluid into the interstitium, and also causes hypertension, favoring plaque rupture. Paradoxical as it may seem, over secretion of tPA may increase cardiovascular risk. This is because tPA degrades the extracellular matrix, causing vascular stiffness that increases cardiac workload, and thus oxygen requirements. Anxious patients with conditions associated with increased plasminogen activator inhibitor-1 levels, such as depression or postprandial hyperinsulinemia, are at high risk of thrombosis. Postprandial hyperinsulinemia may result from consumption of high-carbohydrate foods, considered anxiolytic, combined with a sedentary life, which is common among anxious individuals. Preliminary evidence suggests that high anxiety combined with either depression or a lifestyle that results in hyperinsulinemia has an important role in the pathogenesis of thrombotic events currently classified as unprovoked.
Keywords: anxiety; bleeding; depression; diet; sedentary; thromboembolism